Boundary-value problem for a parabolic system of integro-differential equations with integral conditions - Danylyuk, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Using operators of fractional integration and differentiation, we prove a theorem on the wellposedness of a general parabolic boundary-value problem for a system of integro-differential equations with integral operators in boundary conditions.